Getting Ready for the Human Phenome Project: The 2012 Forum of the Human Variome Project. Issue 4 (20th March 2013) - Oetting, William S.; Robinson, Peter N.; Greenblatt, Marc S.; Cotton, Richard G.; Beck, Tim; Carey, John C.; Doelken, Sandra C.; Girdea, Marta; Groza, Tudor; Hamilton, Carol M.; Hamosh, Ada; Kerner, Berit; et al.
ABSTRACT A forum of the Human Variome Project (HVP) was held as a satellite to the 2012 Annual Meeting of the American Society of Human Genetics in San Francisco, California. The theme of this meeting was "Getting Ready for the Human Phenome Project." Understanding the genetic contribution to both rare single‐gene "Mendelian" disorders and more complex common diseases will require integration of research efforts among many fields and better defined phenotypes. The HVP is dedicated to bringing together researchers and research populations throughout the world to provide the resources to investigate the impact of genetic variation on disease. To this end, there needs to be a greater sharing of phenotype and genotype data. For this to occur, many databases that currently exist will need to become interoperable to allow for the combining of cohorts with similar phenotypes to increase statistical power for studies attempting to identify novel disease genes or causative genetic variants. Improved systems and tools that enhance the collection of phenotype data from clinicians are urgently needed. This meeting begins the HVP's effort toward this important goal.